K- and Cu-doped CaTiO3-based nanostructured hollow spheres as alternative catalysts to produce fatty acid ethyl esters as potential biodiesel - Lanfredi, Silvania [UNESP]; Matos, Juan; Silva, Suzane Rosa da [UNESP]; Djurado, Elisabeth; Sadouki, Ahmed S.; Chouaih, Abdelkader; Poon, Po Shan; González, Eduardo René Pérez [UNESP]; Nobre, Marcos Augusto de Lima [UNESP] (Elsevier, 2020)
New functional polycation oxide-type catalysts were synthesized by the ultrasonic spray-pyrolysis method. The catalytic activity in the production of fatty acid ethyl esters (FAEE´s) using soybean oil was studied. Catalysts are conformed by nanostructured hollow spheres of low density with a stoichiometric formula Ca1-KxTiCux/2O3. The influence of the substitutional ratio (x) upon the catalytic activity was verified. The Ca1-xKxTiCux/2O3 sample with x=0.3 showed the highest activity with a yield up to 89 % to produce fatty acid ethyl esters (FAEE´s) after 24h reaction using 15wt.% catalysts, 120°C and 40bars. The enhancement in the activity was ascribed to the substitution of the Ca+2 sites by K+ and Ti+4 by Cu+2 and to the hollow morphology favoring a more effective interaction between the soybean oil and the active basic sites of the catalysts.
Keywords: FAEE´s synthesis; CaTiO3-based catalysts; Ultrasonic spray pyrolysis; Hollow spheres; K- and Cu-doping